Auditor’s specialization and audit fee in military-connected firms - Almira Zuniga Setiadi; Iman Harymawan (Jurnal Akuntansi dan Auditing Indonesia, 2020)
The aim of this research is to analyze the association among auditor industry specialization, military connection, and audit fee. This study used 790 observations from 227 different firms that were listed in Indonesian Stock Exchange for the period 2010 to 2017. The analysis technique used in this research was Ordinary Least Square Regression analysis model processed with STATA 14.0 software. This study has found that auditor industry specialization is positively and significantly related to audit fee. The results indicated that the auditors perceived their specializations as a product differentiation which increased audit quality conducted, hence audit fee.